Pengaruh Blended Learning terhadap Motivasi Belajar dengan Digital Literacy Sebagai Variabel Mediasi - Anisa Fitri; Muhammad Wildan Shohib; Muh. Nur Rochim Maksum (LP. Ma'arif Janggan Magetan, 2024)
Motivation is the main key to the success of the education and teaching process. Therefore, it is necessary to explore more deeply what are the important factors in fostering learning motivation. Learning motivation can be grown through things that are related or directly related to student interactions on campus, such as the friendship environment, digital literacy, or the learning methods used. The purpose of this study is to determine the effect of Blended Learning on Learning Motivation and the effect of Digital Literacy as a mediating variable between the independent variable and the dependent variable. In addition, this research is expected to add insight in the field of education in order to improve things that can affect learning motivation. This type of research is field research and uses quantitative methods. This study involved 100 respondents from Islamic Religion students at Muhammadiyah University of Surakarta. The results of this study indicate a positive and significant influence between Blended Learing on Learning Motivation, and also a positive and significant effect of the influence of Digital Literacy as a mediating variable between the independent variable (Blended Learning) and the dependent variable (Learning Motivation).